Insights into the habitat of deep diving odontocetes around a canyon system in the northeast Atlantic ocean from a short multidisciplinary survey. (May 2020) - Breen, Patricia; Pirotta, Enrico; Allcock, Louise; Bennison, Ashley; Boisseau, Oliver; Bouch, Paul; Hearty, Aisling; Jessopp, Mark; Kavanagh, Ailbhe; Taite, Morag; Rogan, Emer
Abstract: Several species of deep-diving odontocetes, including beaked whales, sperm whales and pilot whales, are associated with steep continental slope habitat in the northeast Atlantic, where they feed on cephalopods and meso-bathypelagic fish. Some species such as sperm whales are listed as vulnerable by the IUCN red list, whilst many beaked whale species are listed as data deficient, therefore, understanding their habitat is key for their successful conservation. A six-day survey was carried out in November 2017 to characterise the habitat of deep-diving odontocete species in this region by sampling multiple aspects of the ecosystem, from oceanographic features through to prey and predator distributions. Sampling of odontocete occurrence was carried out using both visual and acoustic surveys, supported by ten stations that sampled conductivity, temperature, fluorescence and zooplankton; at five of these stations, fish and cephalopod communities were also sampled during dusk and dawn to a maximum depth of 356 m. Results showed that temperature, salinity, and fluorescence were stable throughout the study area. Zooplankton were dominated by copepods, fish were dominated by myctophids, whilst cephalopods were dominated by Todarodes sagittatus and two Histioteuthis spp. Pilot whales, sperm whales and Sowerby's beaked whales were detected both acoustically and visually, along with other delphinids in large numbers, providing evidence that the study covered rich foraging habitat for these species, especially along the 1000 m–2000 m deep continental slope. Highlights: Odontocetes were regularly sighted and vocally detected in the region. Sowerby's beaked whales were recorded vocalising between 324 m - 840 m. The continental shelf slope west of Ireland is important habitat for odontocetes. Odontocetes are feeding on mesopelagic fish and cephalopods in the region.